LITERACY FINANCIAL TECHNOLOGY THROUGH THE USE OF MICROSOFT EXCEL - Raina Linda Sari; Paidi Hidayat; Inggrita Gusti Sari Nasution; Yola Anggia (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2023)
The purpose of this community service in the form of financial literacy training through Microsofr Excel integration is to improve understanding of financial management priorities and apply Microsoft Excel features to manage finances for Sekolah Indonesia Bangkok junior and senior high school students. Each participant received a training kit, in the form of practical worksheets and goodie bags containing stationery and guidance modules. Worksheets and guide modules are sustainable, so that students can apply them in life outside the training session. The learning methods used in the training are project-based learning and interactive discussions. First, learners get an understanding of the concept of financial management priorities, then proceed with Microsoft Excel practice. The final evaluation is done through the final worksheet results and question and answer activities that cover the cognitive, psychomotor, and affective aspects of the learners. The result of this training is that students understand the concept of financial management priorities in theory, apply Microsoft Excel features, and integrate financial management with Microsoft Excel features.